Freshwater Bivalves of commercial importance in Western Ghats - Jha, Ghanshyam N.; Dar, Bilal A.; Sarkar, Priyanka; Singh, Virender (Indian Farming, 2015)
A study was made with NAIP funding support to investigate thediversity of freshwater molluses in the rivers of Western Ghats ofMaharashtra. These bivalves are not only of commercial value for use as human food but are very important for other reasons as well, hence made a part of the study. The freshwater bivalves have proved to be the best and cheap source of nutritions food.